Sensitive fluorescence detection of lysozyme using a tris(bipyridine)ruthenium(ii) complex containing multiple cyclodextrins. Issue 30 (17th March 2015) - Zhang, Fan; Zhao, Ying-Ying; Chen, Hong; Wang, Xiu-Hua; Chen, Qiong; He, Pin-Gang
Abstract : A new series of metallocyclodextrins with increased fluorescence intensity upon binding with ssDNAs/aptamers has been demonstrated to sensitively detect lysozyme. Abstract : A new series of photoactive metallocyclodextrins with increased fluorescence intensity upon binding with ssDNAs/aptamers has been demonstrated to sensitively and selectively detect lysozyme. The detection mechanism relies on the formation of an aptamer–lysozyme complex, which leads to reduction of fluorescence intensity.